Exploring Student Engagement in STEM Education through the Engineering Design Process - Sulaeman, Nurul Fitriyah; Putra, Pramudya Dwi Aristya; Mineta, Ippei; Hakamada, Hiroki; Takahashi, Masahiro; Ide, Yuhsuke; Kumano, Yoshisuke (Jurnal Penelitian dan Pembelajaran IPA, 2021)
While the engineering is expected to be a catalyst for integrated STEM education, engineering is also problematic, especially in countries with a fixed and centralized curriculum such as Japan. Therefore, translating the framework of integrated STEM into practice and exploring students’ engagement are essential. This study explored students’ engagement in STEM activities through the Engineering Design Process (EDP) in an elective science class. Our participants were sixteen students (aged 14–15) in a Japanese junior high school (JHS) that chose to participate for one semester. Through a single case study, we analyzed the students’ engagement with the activities from the individual and group perspectives. Data from self-assessments, worksheets, presentations, and videos of lessons were collected and analyzed. The results showed that the students’ level of engagement was very high. Exploration with co-occurrence network analysis showed that students’ engagement was associated with the topic of the activity, designing activity, and students’ relationships with their peers. An engineering element in an elective science class was valuable for JHS students and provided a way to enhance science lessons. Also, EPD facilitated essential skills in design and collaboration. Further research in balancing group and individual perspectives is needed.